The Digital Footprint of Water Awareness: Google Trends and Dam Levels in Türkiye - Küllahcı, Kübra (Fırat University, 2026)
As pressures on water resources intensify globally, monitoring not only physical systems but also societal behaviors have become a critical necessity for sustainable management. This study aims to explore whether there is a temporal relationship between dam levels in Türkiye and public information-seeking behavior reflected in digital search trends. In this context, daily dam levels from ten major dams in Istanbul were aggregated into monthly averages to create a representative time series for the city. This series was then matched with monthly Google Trends data for the keyword “baraj doluluk” (dam fullness) and standardized using z-score normalization. Seasonal patterns, threshold behaviors, and lagged correlations were analyzed. The findings reveal that digital search interest exhibits statistically significant relationships with reservoir levels, particularly with a time lag of one to two months. The results suggest that user behavior on digital platforms may reflect rising public awareness in response to changes in environmental systems. Accordingly, the study offers an innovative perspective by demonstrating the potential integration of open digital data sources such as Google Trends into socio-hydraulic monitoring frameworks.

Su kaynakları üzerindeki baskılar, küresel ölçekte etkisini artırırken, yalnızca fiziksel sistemlerin değil, toplumsal davranışların da izlenmesi sürdürülebilir yönetim açısından kritik bir gereklilik hâline gelmiştir. Bu çalışma, Türkiye’deki baraj doluluk oranları ile dijital bilgi arama davranışları arasında zamansal bir ilişki olup olmadığını ortaya koymayı amaçlamaktadır. Çalışmada İstanbul’daki 10 baraja ait günlük doluluk verileri aylık ortalamalar üzerinden birleştirilerek, kenti temsil eden bir baraj doluluk serisi elde edilmiştir. Bu veri seti, “baraj doluluk” anahtar kelimesine yönelik Google Trends verileriyle eşleştirilmiş ve z-normalizasyon yöntemiyle ölçeklendirilmiştir. Elde edilen veriler üzerinden mevsimsel eğilimler, eşik davranışları ve zaman gecikmeli korelasyonlar analiz edilmiştir. Bulgular, dijital arama eğilimlerinin baraj doluluk oranlarıyla özellikle 1–2 aylık gecikmeyle anlamlı ilişkiler taşıdığını ortaya koymuştur. Sonuçlar dijital platformlardaki kullanıcı davranışlarının, çevresel sistemlerdeki değişimlere karşı gelişen toplumsal farkındalığın bir yansıması olabileceğini göstermektedir. Bu bağlamda çalışma, açık dijital veri kaynaklarının sosyo-hidrolik izleme süreçlerine entegre edilebileceğini göstererek literatüre yenilikçi bir katkı sunmaktadır.
Su Farkındalığının Dijital İzi: Google Trends ve Baraj Doluluğu Türkiye Örneği
Keywords: Water Resources Engineering; Su Kaynakları Mühendisliği; Water Resources and Water Structures; Su Kaynakları ve Su Yapıları